(untitled) (Saúde Ética & Justiça, 1999)
The authors present brief hystorical review about important methods of tanatoconservation, specially about tecnics of tanatopraxia, embalming and formolization. They talk over the present legal rules in Brazil, in federal, state and city sphere concerning to the subject. They discuss the sanitary, ethical and legal aspects whith leads the methods used for artificial conservation of corpses.